Bencana sebagai Konstruksi Kekuasaan: Krisis Ekologi di Pulau Sumatera dalam Perspektif Governmentality Michel Foucault - Hasan Afandi, Ahmad; Heru Widodo, Mochammad; Noer, Shobirin (MAJAPAHIT POLICY, 2025)
The phenomenon of natural disasters on the island of Sumatra shows a significant shift from the dominance of geological disasters to an increase in ecological and hydrometeorological disasters, such as floods, landslides, and forest and land fires. This shift indicates that disasters can no longer be understood solely as natural events, but rather as manifestations of ecological crises produced by human activities, exploitative development policies, and weak environmental governance. This study aims to analyze the phenomenon of natural disasters in Aceh, North Sumatra, and West Sumatra from the perspective of Michel Foucault's thinking, particularly through the concepts of power/knowledge and governmentality. This study uses qualitative methods with a Foucauldian literature study and critical discourse analysis approach, by examining books, scientific journals, policy documents, and institutional and media reports. The results of the study indicate that the dominant disaster discourse tends to naturalize disasters and obscure the economic-political power relations that produce ecological crises. The practice of environmental governmentality positions local communities as adaptive subjects to risk, while the structural roots of environmental damage are maintained. This study emphasizes the importance of a critical approach to deconstructing the dominant regime of truth and promoting more just, participatory, and sustainable environmental governance.